Jamaica : Accounting and Auditing - World Bank (Washington, DC, 2013)
This report assesses both the mandatory requirements and the actual practices of the accounting and auditing professions in Jamaica, using the International Accounting Standards (IAS) and the International Standards of Auditing (ISA) as benchmarks. The assessment was conducted using a diagnostic tool developed by the World Bank under a joint initiative of World Bank and International Monetary Fund on the Reports on the Observance of Standards and Codes (ROSC). The Institute of Chartered Accountants of Jamaica (ICAJ) initially carried out a self-assessment with the assistance of an international consultant, to prepare the ground for obtaining financial assistance under the Multilateral Investment Fund program of the Inter-American Development Bank.